Short dual antiplatelet strategy following left atrial appendage closure with Watchman and Watchman FLX: 1-year outcomes. (24th May 2021) - Briosa E Gala, A; Pope, MTB; Monteiro, C; Leo, M; Betts, TR
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Left atrial appendage occlusion (LAAO) is an effective stroke prevention strategy in patients with non-valvular atrial fibrillation and high bleeding risk. Oral anticoagulation or dual antiplatelet (DAPT) therapy is recommended for the period of device endothelisation but confers an increased bleeding risk. Purpose: This study sought to examine the one-year outcomes of a short DAPT strategy following LAA occlusion in a large UK tertiary centre. Methods: This retrospective study included all patients discharged on a short DAPT strategy (6-8 weeks) following a LAAO device implantation from January 2010 and December 2020 in our institution. Medical notes, procedural, and imaging reports were reviewed and adverse event rates were calculated at one year. Yearly bleeding risk was extrapolated from the Swedish National Cohort study according to CHA2DS2-VASc and HASBLED score. Results: A total of 140 patients (106 Watchman and 36 Watchman-FLX) were discharged on a planned short DAPT strategy (age 74 ± 9 years, 70% male, 71% had previous bleeding on OAC, 95% previous major or life-threatening bleeding episodes, 52% previous ischaemic stroke, CHA2DS2-VASc score 4.5 ± 1.2, HASBLED score 3.2 ± 0.7). The median time to switching to either single antiplatelet (APT) or no ATP was 62 days. After first follow-up, 90% were either on SAPT (46.3% aspirin and 39.3% clopidogrel) or no ATP (6.4%). Seven (5%) patients had device-related thrombus on transoesophageal echocardiography and were started on anticoagulation and 4 (3.5%) patients remained on DAPT. At one year, of the 129 patients on a short DAPT strategy the composite of death, ischaemic stroke and non-procedural bleeding occurred in 11 patients (KM 8.9%; 95% CI, 3.7% -13.8%).  Four patients (3.1/100 patient-years) suffered a major bleed and 3 (2.3/100 patient-years) had an ischaemic stroke on SAPT (mean time of 315 days). Compared to estimated annual stroke and bleeding risk adjusted for CHA2DS2-VASc and HASBLED score, this represents a 65% and 38% relative risk reduction in ischaemic stroke and major bleeding, respectively. Conclusion: In our cohort, a short DAPT strategy following LAAO device appears safe with reduction of both thromboembolic and major bleeding events at 1-year.